The Influence of Independent Curriculum on Critical Thinking and Creativity of Students in Elementary Schools - Agustinus Tanggu Daga; Palli Poti; Paulus Ngailo (MASI Mandiri Edukasi, 2025)
This research aims to determine the effect of the Independent Curriculum on critical thinking skills and creativity in elementary school students. This research uses a survey method and collects data with valid and reliable questionnaires. Data analysis includes descriptive analysis, ANOVA analysis, and determination test. Data analysis is the score of the implementation of the Independent Curriculum of 90.15 with a very good classification, a critical thinking score of 37.89, and a creativity score of 50.85 with a less classification, the implementation of the independent curriculum has a positive effect on critical thinking and student creativity, and the magnitude of the influence is 67.4% on critical thinking and 49.4% on student creativity. Although the implementation of the Independent Curriculum is classified as very good, the increase in critical thinking and creativity of students is still classified as less. For this reason, teachers must improve their skills in implementing learning to stimulate critical thinking and student creativity, educational institutions must synergize with stakeholders to improve teacher capacity with sustainable programs, and provide facilities that support the implementation of the independent curriculum in the Loura District